A Four-Pillared Holistic Model for Improving Performance in Engineering Virtual Project Teams. Issue 2 (2nd April 2020) - Lumseyfai, Josh
Abstract: The adoption of virtual teams across engineering organizations continues to rise, given the added benefits compared with co-located teams. However, virtual teams face additional challenges related to managing tasks, communication, and collaboration, requiring distinct facilitation practices for efficient governance. Engineering leaders and organizations should be aware of such practices to enable successful outcomes of their virtual teams. This research presents a four-pillared holistic model for enabling successful virtual project team performance. The model is built on four pillars: (i) Governance Methodology, (ii) Human Interaction, (iii) Technology Management, and (iv) Organizational Environment. A research construct was established to determine the correlating relationships and predictive capabilities between the four model pillars and project performance. The research findings confirmed that each pillar has a strong, positive correlation with project performance, and overall, all four pillars are positive predictors of the performance of a project. Discussion of the results, along with the implications for engineering managers, stakeholders, and organization leaders are presented along with the study limitations and areas for future research.